Carbon Monoxide Concentration Forecasting Using' Hybrid Radial Basis Function Network. - Mamat, Mazlina; Mashor, Mohd. Yusof; Saad, Abdul Rahman; Sadullah, Ahmad Farhan (2003)

(untitled)
Neural network has been renown for its applications in many fields of research especially related to pattern recognition. In this paper, Hybrid Radial Basis Function (HRBF) Neural Network will be exploited to carry out the Carbon Monoxide forecasting.